(untitled) (Revista Brasileira Multidisciplinar, 2024)
This work seeks to evaluate and promote the environmental perception of the various actors in a school community (school management, teachers, employees, lunch ladies, parents and students) using as an instrument the proper management of solid waste generated in the preparation of school meals for the creation of vegetable gardens and composting. The research method uses a qualitative and quantitative approach obtained by applying a semi-structured questionnaire through open and closed questions based on experience that exposes the knowledge, the environmental perception of the actors involved regarding issues of sustainability and environmental education. After content analysis of the participants’ answers and with the discursive textual analysis, initiatives can be promoted for the consumption and correct disposal of organic solid waste, with the purpose of producing understandings about discourses and environmental perceptions. The results showed that the environmental perception of the actors involved was positive, however, it still requires the development of practical interventions, in order to promote a continuous and interdisciplinary EE, since the school is a space that contributes to the formation of actors social workers who will be able to act in the most varied spaces and formations in society, committing themselves to care, ethics, values ​​in the preservation and recovery of environmental spaces, allowing a better quality of the environment and for the various forms of life on the planet.